Figurative Language Used in Taylor Swift’s Album Evermore - Faiza Hudzaifah; Heri Heryono (Jurnal Sinestesia, 2023)
The purposes of the paper are to share insights about figurative meanings that turned out to be very likely to be learned through a song. In addition, to listening to songs for personal enjoyment, it turns out that the songs can also be learnt with the insights such as figurative meanings and also new vocabulary, especially students who major in English. The data collected from five songs on Taylor Swift “Evermore” album. The method used in the paper is the data collection method. Furthermore, qualitative method used for data analysis. The main theories used for data analysis based on the theory of figurative language. The results of this study demonstrate that the meaning of figurative language is much deeper and more impressive rather than lexical meaning.